2017
DOI: 10.1520/jte20160401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nano-ZnO Dispersed State in Bitumen with Digital Imaging Processing Techniques

Abstract: Nano-ZnO can be used as the tracer material to mark the asphalt, and the dispersion of nano-ZnO in the asphalt has an important impact on the mark effect; thus, it is important to study the dispersion state of nano-ZnO in asphalt. In order to achieve this goal, a method of sample preparation to make the nano-ZnO particle exposed to the asphalt surface, and a method for evaluating the dispersion state of nano-ZnO based on digital image processing technique, were put forward in this paper. In this quantitative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, the interfacial bonding strength between nanomaterial and asphalt binder is relatively weak due to their different interfacial properties; interfacial defects form easily between organic and inorganic materials, thus resulting in nanocomposites' performance degradation [11][12][13]. Some factors also increase the difficulties of dispersion and stability on the microscopic scale, such as the high viscosity of asphalt and the agglomeration of nanoparticles (NPs) with high surface energy [14,15]. Previous research found that NPs exist in the form of agglomerates or cause local enrichment or segregation due to the above problems, thus resulting in uneven microstructure of the composite material and distortion of the force field, which not only affects the normal function of the nano effect, but also sometimes plays an opposite role [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the interfacial bonding strength between nanomaterial and asphalt binder is relatively weak due to their different interfacial properties; interfacial defects form easily between organic and inorganic materials, thus resulting in nanocomposites' performance degradation [11][12][13]. Some factors also increase the difficulties of dispersion and stability on the microscopic scale, such as the high viscosity of asphalt and the agglomeration of nanoparticles (NPs) with high surface energy [14,15]. Previous research found that NPs exist in the form of agglomerates or cause local enrichment or segregation due to the above problems, thus resulting in uneven microstructure of the composite material and distortion of the force field, which not only affects the normal function of the nano effect, but also sometimes plays an opposite role [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…When the PPA stoichiometry was small, the storage stability of SBS-modified asphalt was improved. When PPA exceeded its optimum content, serious segregation occurs in the composite-modified asphalt [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Although asphalt binder has inherent self-healing ability, the ability was limited under the action of continuous traffic loading, moisture ingress and other factors. Thus, continuous development of cracks will lead to bitumen pavement failure [5,6,7,8,9]. It is urgent to improve the self-healing of asphalt to extend the service life and reduce maintenance cost of asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%